Efektivitas Pelaksanaan Program Skrining Kesehatan Mental Remaja oleh Puskesmas Nanggalo Kota Padang - viona azzahra; Malse Yulivestra; Ilham Aldelano Azre (Jurnal Administrasi dan Kebijakan Publik, 2026)
Addolescent mental health problems are increasing, while early detection in primary health care remains limited. The Nanggalo Public Health Center in Padang is one of the public health centers that implements an adolescent mental health screening program conducted in schools using various tools, includig the PENDEKAR application innovation. This study aims to analyze the effectiveness of the adolescent mental health screening program implementation at the Nanggalo Public Health Center. A descriptive qualitative approach was used, with data collected through interviews, observation, and documentation. Informant consisted of mental health program managers and school representatives. Program effectiveness was analyzed using Duncan’s theory, including goal attainment, integration, and adaptation. The results show that the screening program has connducted early dtection activities but has not achieved optimal effectiveness. Goal attainment is limited to identification without consistent follow-up services. Integration between the health center and schools exists but is not evenly implemente or formally structured. Program adaptation through screening tools and implementation adjustments reains contrained by limited mental health personnel and resources. It is concludes taht the effectiveness of the adolescent mental health screening program at the Nanggalo Public Health Center is not yet effective according to Dncan’s criteria and requires strengthening of follow-up systems,cross-sector collaborationand institutional support